Entrelinhas do patrimônio: memórias de gerações na Praça Cívica em Goiânia - Anjos, Robson Vieira dos (2019)
This paper aims to reflect on the patrimony discourses used in the process of requalification of the Civic Square in Goiânia (Go). To this end, it uses narratives presented by actors who witnessed transformations that the public space has undergone in recent years, especially since 2003 when the Iphan (Institute of National Historical and Artistic Patrimony) approved the Dumping Dossier of the Architectural Collection and Urban Art Deco of Goiânia, consisting of a set of 22 public buildings and monuments, considered one of the most significant in Brazil. The ethnographic narrative occurs mainly through the memories of Mr. Joaquim Santana, and also of his son Márcio Carvalho, who established a kiosk where he worked and lived for over five decades. Among the elements that make up this research is the place (the kiosk), the memories, narratives and the unfolding of the patrimonial policies.